Doryctobracon areolatus (Szépligeti, 1911) (Hymenoptera: Braconidae): larvae parasitoid of Anastrepha obliqua (Macquart) (Diptera: Tephritidae), in Psidium guajava L. fruits (Myrtales: Myrtaceae) (Aporte Santiaguino, 2022)
Anastrepha obliqua (Macquart, 1835) (Diptera: Tephritidae), known as the West Indian fruit fly, is a widely distributed species in America. Due to its polyphagous capacity, this insect is of great economic importance, which is studied based on its distribution, forms of management and control. Doryctobracon areolatus (Szépligeti, 1911) (Hymenoptera: Braconidae), a native species, solitary endoparasitoid, koinobiont, has a wide distribution in the Neotropics and subtropics, and due to its capacity as a parasitoid of the genus Anastrepha is a potential candidate for the natural control of this pest. The species Psidium guajava L., native to Mexico, is a fruit with high nutritional value and has great relevance from the commercial perspective. In Panama, the information related to the Parasitoid-Anastrepha-Fruit relationship in this species is limited, so it is of high value to establish research baselines to better understand these relationships to create programs for the biological control and management of this pest and achieve export standards. A total 43 larvae of A. obliqua where collected from guava fruits with evidence that the parasitoid D. areolatus introduced its ovipositor repeatedly. The samples were taken to the Laboratory of Venomous Arthropods of the G. B. Fairchild Invertebrate Museum of the University of Panama. A total of 40 adult individuals of A. obliqua were obtained, 34 females and 6 males (female/male ratio of 5:1); and larvae presented a 93% survival. Also, three individuals of D. areolatus were obtained from one of the fruits of P. guajava, where D. aerolatus introduced its stinger, previously at the collection site. In conclusion, D. areolatus has potential as a biological control agent for A. obliqua, although it needs to be complemented with other integrated management alternatives.
Keywords: Anastrepha obliqua; Doryctobracon areolatus; Panama; Parasitoid; Psidium guajava